RESEARCH ON ACOUSTIC RADIATION CHARACTRRISTICS OF PERIODIC PERFORATED DAMPING SANDWICH PLATE - ZHOU JingDong; WEN Yao; CHEN Yuan; LIU MingYong; LIU Yang (Jixie qiangdu)
Base on the principle of damping reduction vibration and reference the periodic boundary conditions,through the acoustic bridge vibration energy transfer, this paper established a double-layer plate with the opening damping model;Considering the frequency-dependent properties of viscoelastic,through the finite element and boundary element numerical algorithm of calculating the radiation sound power,analyzes the periodic perforated damped sandwich plate structure acoustic radiation characteristics. Numerical calculation results show that in low and middle frequency band,periodic perforated damping sandwich plate can not only reduce the double plate radiating acoustic power,but also can reduce the use of damping materials,optimization of the whole structure of weight; Analyses the porosity and periodicity of the periodic opening damped sandwich plate structure influence the double layer plate structure acoustic radiation,found the inhibition of sandwich plate of acoustic radiation of the optimal opening porosity and periodicity,and the conclusion is verified by the experiments.